The Role of C1-Esterase Inhibitors in the Management of Vasogenic Edema in Glioblastoma - Gillian R. Naro; Nicholas Noverati; Timothy Craig (Case Reports in Medicine)
Glioblastoma (GB) is one of the most common adult primary brain tumors, classified as a grade IV astrocytoma and highly malignant in nature. As the tumor grows and disrupts the blood-brain barrier (BBB), vasogenic edema can result. The edema has the potential to significantly contribute to a patient’s morbidity and mortality. Bradykinin has been theorized to play a role in this process as well as encourage tumor spread. Here we discuss a case in which a patient with vasogenic edema and angioedema refractory to antihistamines and high dose corticosteroids responded to C1-esterase inhibitor (C1INH) therapy. Though data exist concerning the role of bradykinin in GB, no clinical studies using C1INH have been done in humans with GB.